Assessing in-service teachers self-efficacy towards teaching thinking skills in Iran - Dimajani, Fatemeh Sharif (Kulliyyah of Education, International Islamic University Malaysia, 2014)
This study examined in-service teachers' level of self-efficacy with respect to their teaching thinking skills in the cities of Rasht and Tehran, Iran. It also investigated the relationship between teachers' self-efficacy and their abilities to conduct teaching thinking skills in the selected schools. Finally, this study examined gender and location differences in the two mentioned areas. The participants were 230 in-service teachers from the two selected cities in Iran. Data was collected through purposive sampling procedure by using a modified instrument developed by Tebbs (2000), entitled The New Millennium in Mind. The results of the study illustrated that the teachers' level of self-efficacy were on the average. Most of the respondents were not fully confident in terms of their abilities and skills towards teaching thinking skills. Their knowledge towards thinking skills, and information about different methods, models and activities for teaching these skills were not adequate due to insufficient and less qualified training. Difference in self-efficacy level was clearly seen between two geographical locations. Accordingly, investment in qualified professional development programs with special focus on teaching thinking skills would be highly recommended.